Inmunidad contra fiebre aftosa, reactores al antigeno via y portadores en bufalos indues - Arbelaez R., G.=700 1 Pinto, A.A.; Casas O., R.
(En, Es)
ilus., 18 ref.
Keywords: FIEBRE AFTOSA; ENFERMEDADES INFECCIOSAS; GANADO BOVINO; INMUNIDAD; MORBOSIDAD; COLOMBIA